Feasibility of learning videos on nutrient subtopics - Putri Anggini; Ruqiah Ganda Putri Panjaitan; Titin Titin (Biosfer: Jurnal Pendidikan Biologi, 2026)
This study aims to develop and assess the feasibility of learning video media on the sub-topic of food substances based on the results of an inventory of medicinal plants that increase appetite in toddlers. The research method used is Research and Development (R&D) with reference to the Borg and Gall model which is limited to five stages, namely potential and problems, data collection, product design, design validation, and design revision. Media validation was carried out by five validators using a purposive sampling technique with assessments on aspects of format, content, language, and appearance. Validity analysis uses the Aiken's V formula, while reliability is explained using the Intraclass Correlation Coefficient (ICC) method. The results of the study showed that the learning video media obtained an overall validity value of 0.92 with a valid category. The results of the reliability test showed a value of 0.733 with a moderate category. Based on these results, the learning video media on the sub-topic of food substances is declared suitable for use as a biology learning medium, although further testing is still needed to determine its effectiveness in improving student learning outcomes.